2019
DOI: 10.3390/ijms20123102
|View full text |Cite
|
Sign up to set email alerts
|

Tandem 13-Lipoxygenase Genes in a Cluster Confers Yellow-Green Leaf in Cucumber

Abstract: Some lipoxygenase (LOX) isoenzymes can co-oxidize carotenoids. Carotenoids are collectors of light energy for photosynthesis and can protect plants from reactive oxygen species and coloration. This study isolated the cucumber (Cucumis sativus L.) yellow-green leaf mutant (ygl1), which had yellow-green leaves with decreased chlorophyll synthesis, increased relative carotenoid content, and delayed chloroplast development. Genetic analysis demonstrated that the phenotype of ygl1 was caused by a recessive mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
(79 reference statements)
0
30
0
Order By: Relevance
“…Moreover, over half of the ClLOX genes (10 in 16) were identified as tandemly duplicated genes, indicating that tandem duplication events are the main driving force for the evolution of ClLOX genes. This feature has also been found in some other plants, such as poplar [11], maize [16], tomato [18], cucumber [34], and radish [15]. In addition, according to the collinear module of watermelon and Arabidopsis, all of the six AtLOX genes have syntenic copies in ClLOX genes (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, over half of the ClLOX genes (10 in 16) were identified as tandemly duplicated genes, indicating that tandem duplication events are the main driving force for the evolution of ClLOX genes. This feature has also been found in some other plants, such as poplar [11], maize [16], tomato [18], cucumber [34], and radish [15]. In addition, according to the collinear module of watermelon and Arabidopsis, all of the six AtLOX genes have syntenic copies in ClLOX genes (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 52%
“…As compared with the normal green plants, 9110Gt and vyl mutant could grow up to the same or slightly smaller plant height. The ygl1 mutant was a spontaneous mutant isolated from inbred cucumber 1402, which was slightly smaller than the wild type throughout the developmental stage ( Ding et al, 2019 ). The C777 mutant displayed yellow color in cotyledons and true leaves with stay-green dots at emergence.…”
Section: Discussionmentioning
confidence: 99%
“…The virescent leaf trait had also been reported to be controlled by one single recessive nuclear gene in some other plants, such as Arabidopsis thaliana ( Ma et al, 2017 ; Huang et al, 2018 ), rice ( Wang et al, 2016 ; Zhu et al, 2016 ), cotton ( Zhu et al, 2017 ; Mao et al, 2019 ), maize ( Xing et al, 2014 ), cabbage ( Liu et al, 2016 ), apple ( Fernández-Fernández et al, 2014 ), watermelon ( Zhang et al, 1996 ) and so on. In cucumber, the virescent traits in 9110Gt ( Miao et al, 2016 ), vyl mutant ( Song et al, 2018 ), ygl1 ( Ding et al, 2019 ) and C777 ( Hu et al, 2020 ) were also controlled by one single recessive nuclear gene. It indicated that the virescent mutants were easy to form because the mutation of anyone gene involving in the pathways of chloroplast development or chlorophyll biosynthesis could generate the virescent leaf appearance ( Beale, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations